Interactions between imazethapyr and bovine serum albumin: Spectrofluorimetric study - Pacheco, Maria Emilia (2012)
The interaction between imazethapyr (IMA) and bovine serum albumin (BSA) was investigated by fluorescence spectroscopy. The Stern-Volmer quenching constant (K SV) at three temperatures was evaluated in order to determine the quenching mechanism. The dependence of fluorescence quenching on viscosity was also evaluated for this purpose. The results showed that IMA quenches the fluorescence intensity of BSA through a static quenching process. The values of the binding constant for the formed BSA-IMA complex and the number of binding sites were found to be 1.51×10 5 M -1 and 0.77, respectively, at room temperature. Based on the calculated thermodynamic parameters, the forces that dominate the binding process are hydrogen bonds and van der Waals forces, and the binding process is spontaneous and exothermic. The quenching of protein fluorescence by iodide ion was used to probe the accessibility of tryptophan residues in BSA and the change in accessibility induced by the presence of IMA. According to the obtained results, the BSA-IMA complex is formed in the site where the Trp-134 is located, causing it to become less exposed to the solvent. © 2012 Elsevier B.V. All rights reserved.